Training on Ectomycorrhizal Fungus Inoculant Production Techniques for Agricultural Land at Campus IV, Khairun University - Nur Hikmah; Reyna Ashari; Laswi Irmayanti; Aqshan Shadikin Nurdin (Universitas Muhammadiyah Palembang, 2023)
Khairun University Campus IV is currently being developed as an educational tourism location. One form of activity is developing agricultural land. The problem there is that the land is still not very fertile. Efforts that can be made are by developing ectomycorrhizal inoculants to increase soil fertility. Community service activities are directed at providing training to the community around Campus IV Unkhair in producing ectomycorrhizal inoculants. Ectomycorrhiza has several benefits for plants, namely being able to increase the uptake of P and N nutrients. The series of service activities carried out are providing training and practice in exploring ectomycorrhiza in the forest around the Unkhair campus IV area, training in the production of ectomycorrhizal inoculants, and training in applying ectomycorrhizal inoculants on agricultural land.